Measurement of the forward-backward asymmetries in the production of Ξ and Ω baryons in p p collisions MEASUREMENT of the FORWARD-BACKWARD ⋯ V. M. ABAZOV et al. - Abazov, V. M. (2016)
We measure the forward-backward asymmetries AFB of charged Ξ and Ω baryons produced in pp collisions recorded by the D0 detector at the Fermilab Tevatron collider at s=1.96 TeV as a function of the baryon rapidity y. We find that the asymmetries AFB for charged Ξ and Ω baryons are consistent with zero within statistical uncertainties.